77.2k views
1 vote
-27=-3p+15-3p solve for p

User Nabarun
by
5.9k points

1 Answer

5 votes
-3p + 15 -3p= -27
If we simplify p's ( as -3p + -3p) we will get

15 -6p = -27
We need to leave the unknown "(p)" alone. So you can put -6p both to the left or the right of the equality. You can solve the problem easier when you make the unknown positive and leave it alone.

So;
15 +27 = 6p (We threw it to the other side to make -6p positive)

42 = 6p
7 = p

Hope it helps!
#MissionExam001
User Tyranid
by
5.0k points